Писемні історичні джерела як засіб пізнання морального образу Яна Щасного Гербурта - Цебенко, Олег; Tsebenko, Oleh (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті розглянуто численні історичні писемні матеріали, які можуть слугувати засобом пізнання морального образу видатного представника роду Гербуртів – Яна Щасного. Акцентовано увагу на специфічних особливостях зображення представника роду Гербуртів у різних джерелах, що дало змогу одержати конкретну інформацію. Проаналізовано чималу збірку особистої кореспонденції Яна Щасного Гербурта, яка є важливим писемним джерелом у пізнанні та розкритті образу цього літературного й політичного діяча з Галичини. In the article is considered the numerous historical writing materials, which can be as the instrument for cognition of moral character of famous representative of the Herburts genus Jan Szczasny. Point out at specific features of Herburts genus representatives’ reflection by different kinds of sources, which give a chance to get from the concrete information. The large collection of the personal correspondence of Jan Szczasny Herburt is analyzed, which is an important writing source in getting known of this ambiguous representative of genus. The correspondences are as in the manuscripts of Chartoryski library, and as in the printed works of the Polish authors. The reasonable study of the complex sources and comparison of the given information, gave the possibility to create the generalized moral character of Jan Szczasny Herburt, as a typical representative of the Polish gentry in the end of XVI − beginning XVII centuries.
Historical Writing Sources as the Instrument for Cognition of Moral Character of Jan Szczasny Herburt
Keywords: писемні джерела; моральний образ; Ян Щасний Гербурт; особиста кореспонденція; благодійність; writing sources; moral character; Jan Szczasny Herburt; personal correspondence; charity